Confining Pyrrhotite Fe7S8 in Carbon Nanotubes Covalently Bonded onto 3D Few‐Layer Graphene Boosts Potassium‐Ion Storage and Full‐Cell Applications. Issue 12 (3rd March 2021) - Han, Kun; An, Fuqiang; Wan, Qi; Xing, Lidong; Wang, Lei; Liu, Qiang; Wang, Wei (Alex); Liu, Yongchang; Li, Ping; Qu, Xuanhui
Abstract: The pyrrhotite Fe7 S8 with mixed Fe‐valence possesses high theoretical capacity, high conductivity, low discharge/charge voltage plateaus, and superior redox reversibility but suffers from structural degradation upon (de)potassiation process due to severe volume variations. Herein, to conquer this issue, a novel hierarchical architecture of confining nano‐Fe7 S8 in carbon nanotubes covalently bonded onto 3D few‐layer graphene (Fe7 S8 @CNT@3DFG) is designed for potassium storage. Notably, CNTs could successfully grow on the surface of 3DFG via a tip‐growth model under the catalytic effect of Fe3 C. Such structure enables the hierarchical confinement of 0D nano‐Fe7 S8 to 1D CNTs and further 1D CNTs to 3DFG, effectively buffering the volume variations, prohibiting the agglomeration of Fe7 S8 nanograins, and boosting the ionic/electronic transportation through the stable and conductive CNTs‐grafted 3DFG framework. The as‐prepared Fe7 S8 @CNT@3DFG electrode delivers an exceptional rate capability (502 mAh g −1 at 50 mA g −1 with 277 mAh g −1 at 1000 mA g −1 ) and an excellent long‐term cyclic stability up to 1300 cycles. Besides, the in‐situ XRD and ex‐situ XPS/HRTEM results first elucidate the highly reversible potassium‐storage mechanism of Fe7 S8 . Furthermore, the designed potassium full‐cell employing Fe7 S8 @CNT@3DFG anode and potassium Prussian blue (KPB) cathode delivers a promising energy density of ≈ 120 Wh kg −1, demonstrating great application prospects. Abstract : A novel hierarchical architecture of confining nano‐Fe7 S8 in carbon nanotubes covalently bonded onto 3D few‐layer graphene is designed as a potassium‐ion storage anode for boosting the reversible capacity, rate capability, and cycling stability. The material design along with the admirable electrochemical performance in this work can pave a new avenue for the anode applications of transition metal sulfides in KIBs.